Miniopen Oblique Lateral L5-S1 Interbody Fusion: A Report of 2 Cases - Keijiro Kanno; Seiji Ohtori; Sumihisa Orita; Kazuyo Yamauchi; Yawara Eguchi; Yasuchika Aoki; Junichi Nakamura; Masayuki Miyagi; Miyako Suzuki; Gou Kubota; Kazuhide Inage; Takeshi Sainoh; et al. (Case Reports in Orthopedics)
Extreme lateral interbody fusion (XLIF) has been widely used for minimally invasive anterior lumbar interbody fusion (ALIF), but an approach to L5-S1 is difficult because of the iliac crest. In the current study, we present 2 cases using minimally invasive oblique lateral interbody fusion (OLIF) of L5-S1. The patients showed foraminal stenosis between L5 and S1 and severe low back and leg pain. The patients were placed in a lateral decubitus position and underwent OLIF surgery (using a cage and bone graft from the iliac crest) without posterior decompression. Posterior screws were used in the patients. Pain scores significantly improved after surgery. There was no spinal nerve, major vessel, peritoneal, or urinary injury. OLIF surgery was minimally invasive and produced good surgical results without complications.